GIS, GPS And Dumpy Level Survey for Estimation Of Runoff By SCS-CN Method For VIIT Campus, Visakhapatnam - et. al., Dr. Ch. Kannam Naidu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Globally majority of countries in the worldare worrying about declining of groundwater levels day by day. The one of the best solutions to improve the Groundwater levels is the artificial recharge of Groundwater. The estimation of runoff is very essential for the recharge of Groundwater. Exactly here a study has been madeto estimate the runoff by Soil Conservation Service Curve Number (SCS-CN) method for Vignan’s Institute of Information Technology (VIIT) campus, Visakhapatnam. In this study, the Land Use/Land cover (LU/LC)map of the study area has been extracted using GIS software from the Google Earth Remote Sensing imagery. The ground truth survey has been done using Global Position System (GPS) to update the missing data in the imagery. The Digital Elevation Model (DEM) of the study area has been generated using elevation data which was collected through dumpy level survey along with GPS. The soil texture map has been extracted from Soil Map which was bought from the National Bureau Soil Sciences (NBSS). The rainfall data of the study area has been collected from the nearest Gajuwaka Rain gauge station. The runoff of the study area has been estimated using the SCS-CN method by using the LU/LC, the Soil Texture map and rainfall data. In the present study the year wise total runoff varies from 30.352 mm to 209.445 mm of the study area. The average Annual rainfall of the study area is 1048.84 mm for the years 2009 to 2018. The average annual runoff volumeof the study area for 10 years is 16293.48 Cu.M.The DEM map has been used to derive the mini watersheds to locate the Artificial Recharge locations to recharge the runoff to the Groundwater.